Aplicación de la gestión de almacén para mejorar la productividad en el área de almacén de una empresa comercializadora de harina integral de soya, Trujillo 2021 - Tirado Cerquin, Lennin Edison (2023)
The present research of professional proficiency has shown that the application of warehouse management was necessary, since it contributed to solving the problem and thus achieving the improvement of the productivity of the company's warehouse area. The objective of this research is to improve productivity in the warehouse area of a company that sells whole soy flour through the application of warehouse management, Trujillo 2021. The research is quantitative of a pre-experimental type, since a proposal is applied that is then measured to observe the change; the sample was made up of all the personnel from the warehouse area of the Trujillo-based company, applying tools such as the Ishikawa and Pareto diagrams, flowcharts, in addition to the 5'S checklist. The application of the methodologies lasted six months, following a schedule detailing the different activities carried out, starting with an evaluation, to then carry out the implementation and evaluate productivity, it should be noted that each phase began with training and culminated with your audit, in order to understand if the results of the implementation were optimal. It was concluded that the productivity in the warehouse area of a company that sells whole soybean flour improves through the application of warehouse management, having that the efficiency went from 84% to 95% and the effectiveness from 89% to 93%.